Brief Report: Temporal Changes in HIV Transmission Patterns Among Young Men Who Have Sex With Men, United States, 2009–2016. (1st May 2020) - Panneer, Nivedha; France, Anne Marie; Whiteside, Y. Omar; Zhang, Tianchi; Wertheim, Joel O.; Oster, Alexandra M.
Abstract : Background: In the United States, young men (aged 13–24 years) who have sex with men (MSM) bear a disproportionate burden of HIV. Transmission among MSM has been found to be disassortative by age. Methods: We analyzed HIV-1 pol sequences reported to the US National HIV Surveillance System from MSM with HIV diagnosed during 2009–2016. Using an HIV genetic transmission network, we identified persons with closely related viruses (ie, genetic distance ⩽1.5%) and used multivariable logistic regression to examine changes from 2009–2012 to 2013–2016 in proportions of MSM linked to young MSM who were >5 years older or of the same race/ethnicity. Results: Among 9510 young MSM linked to another MSM with a closely related virus, 37% linked to an older MSM and 62% linked to an MSM of the same race/ethnicity. Comparing 2013–2016 with 2009–2012, we found increases in linkage of older MSM to young MSM, with the most substantial increases seen in Hispanic/Latinos aged 13–19 [adjusted prevalence ratio (APR) = 1.31, 95% confidence interval (CI) = 1.11 to 1.56] and blacks aged 13–19 (APR = 1.23, CI = 1.06 to 1.41) and 20–24 years (APR = 1.14, CI = 1.02 to 1.28). By contrast, change in linkage patterns among racial/ethnic groups was unremarkable. Conclusions: We found evidence of increased age mixing among MSM with respect to HIV transmission over time, which coincides temporally with changes in partner-seeking behavior such as increased use of mobile applications. These findings indicate the importance of social factors on HIV sexual and transmission networks and suggest that prevention efforts need to effectively reach MSM of all ages.